Targeting EGFR in Esophagogastric Cancer - Maron, Steven B.; Xu, James; Janjigian, Yelena Y. (Frontiers in Oncology, 2020)
Esophagogastric cancer (EGC) remains a major cause of cancer-related mortality. Overall survival in the metastatic setting remains poor, with few molecular targeted approaches having been successfully incorporated into routine care to-date – only first line anti-HER2 therapy in ERBB2-expressing tumors, second line anti-VEGFR2 therapy with ramucirumab in unselected patients, and pembrolizumab in PD-L1 expressing or MSI-H patients. EGFR inhibitors were extensively studied in EGC, including phase III trials with cetuximab (EXPAND), panitumumab (REAL-3), and gefitinib (COG). All three trials were conducted in unselected populations, and in doing so, failed to demonstrate clinical benefit. Here we review previous attempts at targeting EGFR in EGC and potential future biomarkers for targeting this pathway in patients with EGFR-amplified tumors.